Instagram as a tool to (de)code spanish poetry in the classroom - Ballester Pardo, Ignacio; Ruiz Flores, Mariana (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article analyzes the social network Instagram with the aim of using it as a means for the teaching of Spanish American poetry in Primary and Secundary classrooms. Not only is attention paid to the de-automation (Víktor Shklovski) of the genre in question, known as difficultism due to its heritage from the Ibero-American neo-avant-garde (Alejandro Palma), but also the digital language for communication that is known in a peaceful way as era of the tradition of rupture (Alejandro Higashi). With all this, we offer a didactic approach with poets like Agustín Fernández Mallo, Vicente Luis Mora, Horacio Warpola, Andrea Alzati, Romina Cazón, Daniela Sol or Valeria Román.